ANALISIS STRUKTUR FUNGSIONAL DAN NILAI SOSIAL BUDAYA DALAM NOVEL “SUARA SAMUDRA CATATAN DARI LAMALERA” KARYA MARIA MATILDIS BANDA - Sofiana Susana; I Gusti Ayu Putu Tuti Indrawati; Ni Luh Sukanadi (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2021)
This research is a descriptive study that aims to find out the functional structureand socio-cultural values contained in the novel “Suara Samudra CatatandariLamalera” by Maria Matildis Banda. The theories that used in this research were (1) the meaning of the novel, (2) the building blocks of the novel, (3) functional structure, and (4) aspects of socio-cultural values. The data was collected by observation, documentation and literature. The data in this research was analyzed using qualitative techniques, Instrument as a media in gathering data hence, all data were arranged systematically. The steps in data analysis using data triangulation analysis, which were (1) data reduction (2) data presentation (3) data verification. The results of this research also indicates the findings of three functional structures, namely the functional structure between Lyra and Arakian, the functional structure between Lyra and Mariana and the functional structure between Arakian and the Lamalera traditional Ritual. The novel “Suara Samudra notes from Lamalera” by Maria Matildis Banda also contains eight aspects of social status. Culture, namely elements of religion, elements of livelihood, elements of technology and traditional equipment, elements of art. elements of knowledge, elements of society, and elements of traditional rituals.